The ESPID/ESWI Joint Symposium—A strong vote for universal influenza vaccination in children in Europe. Issue 49 (8th December 2015) - Kobbe, Robin
Abstract: During this year's 33rd annual meeting in Leipzig, Germany, the European Society of Paediatric Infectious Diseases (ESPID) jointly together with the European Scientific Working group on Influenza (ESWI), organized a staged debate on the motion of universal annual immunization of children against influenza as a cost-effective health intervention in Europe. Six invited speakers, all experts in the field of influenza vaccination, who were not necessary confident with their given position of pro or contra, battled each other with short oral presentations to convince the audience to vote for or against the motion.